Correlative link ages between indices of bone metabolism and thyroid hormones in rats with periodontitis - Vitaliy Shcherba; Andriy Miz; Mariia Kyryliv; Iryna Bekus; Inna Krynytska; Mykhaylo Korda (Kazimierz Wielki University, 2017)
Introduction: It has been established that changes in the bone tissue of the jaw are present in all cases where there are at least small pathological inflammatory changes in the mucous membrane of the oral cavity. This suggests a significantly greater pathogenetic relationship between inflammatory changes in the mucosa and changes in the bone part of the periodontal disease. Despite a large number of studies, the molecular mechanisms of the influence of thyroid hormones on the bone metabolism have not been completely studied.  The aim of study: to clarify mechanisms of the periodontitis development in rats with thyroid dysfunction based on a comparative analysis of the correlations between the bone metabolism indices and the concentration of  thyroid stimulating hormone,  free thyroxine and free triiodothyronine. Material and methods: Experimental studies were conducted on male, nonliner, white rats of around 4 months of age.  The experimental animals were divided into the following groups: І - control animals;  ІІ - animals with periodontitis; ІІІ - animals with periodontitis combined with hyperthyroidism; IV - animals with periodontitis combined with hypothyroidism. Total calcium, ionized calcium, phosphorus, osteocalcin concentration and  activity of phosphatases were measured. Correlation analysis was performed between all the studied indices. Coefficient of linear correlation (r) and its fidelity (p) was calculated that was accordingly denoted in the tables (correlation matrices). The correlation coefficient was significant at p<0.05. Results: The conducted correlative analysis shows that there are different interconnections between the indices of calcium-phosphorus metabolism, bone formation and bone resorption with free triiodothyronine, free thyroxine and thyroid stimulating hormone, in case of the experimental periodontitis combined with thyroid dysfunction. In animals with modelled periodontitis combined with hyperthyroidism, more correlative interactions with triiodothyronine, thyroxine and thyroid stimulating hormone were established compared to the rats of hypothyroid group. Conclusions: Consequently, the thyroid dysfunction significantly affects the parameters of bone metabolism in case of an experimental periodontitis, which requires further research.